(untitled) (Actual Problems of Mind, 2021)
The paper considers T. Reid’s life, philosophical thought, and critical remarks of the Lockean theory of personal identity. This paper can be viewed as a general introduction to T. Reid’s philosophy. The paper consists of several main sections. At first, the article outlines biographical key events biography. The second section of the paper concerns history of creation, structure, ideas and main topics of T. Reid’s magnum opus in epistemology, “Essays on the Intellectual Powers of Man”. Reid refers to the category of identity twice: he considers it as a fundamental category of philosophy and as a feature of a person. The paper considers T. Reid’s critical analysis of the Lockean theory of personal identity. It states that T. Reid tries to give a more precise and explicit definition of “personal identity” in comparison to Locke’s definition. T. Reid defines identity as a continued existence of an intelligent being over time. T. Reid shows that the Lockean view is methodologically inconsistent, as the Lockean definition of a person and views on personal identity contradicts each other. He provides several arguments to show that. They are as follows: (1) identity, based on consciousness, is violated with ease because of forgetfulness; (2) memory cannot be the criteria of personal identity as memory is its evidence; (3) consciousness is mental faculty that distinguishes people from other creatures, but it is the same for all people, so it cannot explain individual differences between two people. The fourth section of the paper considers the concept of “consciousness”. The paper argues that there is a difference in its interpretation by Locke and Reid, which led to T. Reid’s misunderstanding of J. Locke’s philosophical ideas. This difference is the following: for Locke consciousness includes memory and perception, spreads from the past to the present, while for Reid it concentrates exclusively on the present and is different from memory and perception.